Ecophysiology of environmental Aspergillus fumigatus and comparison with clinical strains on gliotoxin production and elastase activity. (1st February 2016) - Alonso, V.; Aminahuel, C.; Díaz Vergara, L.; Pereyra, C.; Poloni, V.; Dalcero, A.; Cavaglieri, L.
Abstract: The aim of this manuscript was to study the influence of water activity (aW ) and pH in the ecophysiological behaviour of Aspergillus fumigatus strains at human body temperature. In addition, gliotoxin production and enzymatic ability among environmental ( n = 2) and clinical ( n = 5) strains were compared. Ecophysiological study of environmental strains was performed on agar silage incubated at 37°C, studying the interaction at eight aW levels (0·8, 0·85, 0·9, 0·92, 0·94, 0·96, 0·98 and 0·99) and eight pH levels (3·5, 4, 4·5, 5, 6, 7, 7·5 and 8). Considering the influence of the assumed lung conditions on growth of A. fumigatus (aW 0·98/0·99 and pH of 7/7·5), the optimal condition for the development of A. fumigatus RC031 was at aW 0·99 at pH 7. At aW 0·98/0·99 and pH of 7/7·5, the highest growth rate and the lowest lag phase was reported, whereas there were no significant differences at aW 0·98/0·99 and pH 7/7·5 interactions on growth of A. fumigatus RC032. Gliotoxin production of A. fumigatus strains was evaluated. The gliotoxin production was similar in clinical and environmental strains. Elastin activity was studied in solid medium, highest elastase activity index was found for clinical strain A. fumigatus RC0676, followed by the environmental strain A. fumigatus RC031. Opportunistic environmental strains can be considered as pathogenic in some cases when rural workers are exposed constantly to handling silage. Significance and Impact of the Study: Aspergillus fumigatus is one of the main opportunist pathogen agents causing invasive aspergillosis. Rural workers present a constant exposition to A. fumigatus spores caused by feed‐borne manipulation. In this study, environmental A. fumigatus strains were able to grow and produce gliotoxin onto the studied conditions including the lung ones. Environmental and clinical strains were physiologically similar and could be an important putative infection source in rural workers.